1993
DOI: 10.1021/ma00067a013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of backbone flexibility on the transitional properties of side-chain liquid-crystalline polymers

Abstract: A new homologous series of side-chain liquid-crystalline polymers has been synthesized, the poly[4- [[a-(4-cyanobiphenylyl-4'-oxy)-ai-alkyl]oxy]styrene]s, and the thermal behavior of the series investigated. The homologues with butyl or longer spacers exhibit a smectic phase, whereas the propyl homologue does not exhibit liquid crystallinity. The properties of these polymers are compared with those containing other polymeric backbones to study the effect of flexibility on thermal behavior. We propose a new mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 8 publications
5
47
0
Order By: Relevance
“…For comparative purposes, the clearing entropies for the monomeric nOCB series are also shown in Fig. 3 [17]. The propyl to nonyl members of this series exhibit a nematic-isotropic transition and the associated entropy change is considerably smaller than that observed for either the odd or even membered dimers.…”
Section: Classification Of Liquid Crystal Dimersmentioning
confidence: 98%
See 3 more Smart Citations
“…For comparative purposes, the clearing entropies for the monomeric nOCB series are also shown in Fig. 3 [17]. The propyl to nonyl members of this series exhibit a nematic-isotropic transition and the associated entropy change is considerably smaller than that observed for either the odd or even membered dimers.…”
Section: Classification Of Liquid Crystal Dimersmentioning
confidence: 98%
“…The dependence of the entropy change associated with the nematic-isotropic transition (d) on the number of methylene units in the¯exible spacer, n, for the BCBOn series [18]. Also shown are the entropy changes associated with the nematic-isotropic (h) and the smectic A-isotropic transitions (j) for the nOCB series [17] phase is insuf®cient to convert bent conformers into linear conformers. Hence, the orientational order is not enhanced and a smaller nematicisotropic entropy would be expected.…”
Section: Classification Of Liquid Crystal Dimersmentioning
confidence: 99%
See 2 more Smart Citations
“…After this discovery, there have been many systematic studies on the effects of the spacer length on the thermal and physical properties of these SCLCPs. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been shown that increasing the spacer length while keeping the backbone and mesogenic groups constant has two effects: (i) the clearing temperature of the polymer increases and (ii) the entropy change associated with the clearing transition decreases. Most of the research work refers to polyacrylate, [33,34] polymethylacrylate, [35,36] polyurethane, [37] and polystyrene [38][39][40][41] backbones.…”
Section: Introductionmentioning
confidence: 99%